24. NURSING STUDENTS’ PERCEPTION OF THE ACADEMIC LEARNING ENVIRONMENT IN THAI BINH OF UNIVERSITY MEDICINE AND PHARMACY IN 2022 (Vietnam Journal of Community Medicine, 2023)
Background: The learning environment has a proven impact on student characteristics such as attitude, learning progress and school health, which can affect learning outcomes and satisfaction. and the success of students. The study aims to assess the feedback of nursing students about the theoretical and clinical learning environment of Thai Binh University of Medicine and Pharmacy. Methods: The descriptive cross-sectional study was performed on 115 4th year Thai Binh University of Medicine and Pharmacy nursing students based on the VCLEI and DREEM questionnaire.Results: Regarding the theoretical environment with 45.2%; 53.9%; 0.9% was a very good response, good response and many problems need to improve, respectively. Reflection about Clinical environment learning had 35.7% very good response, 64.3% good response. The mean scores for the perception of the learning environment ranged from 2-3.5 (the level at which many problems need to improve). The study also shows a significant relationship between gender, student-centered clinical learning attitudes, students’ views about lecturers in theoretical learning, and the desire to study at university with academic results.Conclusion: Nursing students gave good feedback on the theoretical and clinical learning environment of Thai Binh University of Medicine and Pharmacy
Keywords: Reflection, theoretical learning environment, practical learning environment, Thai Binh University of Medicine and Pharmacy.